A Practical Guide to Caries Prevention in Children. (2nd November 2020) - Rashid, Mishaal; Ellis, Amy; Deery, Chris
Abstract : Caries is one of the most common diseases in the world and it is mostly preventable. Caries can have a large impact on a child's physical, social and mental health. There are a number of clinical interventions available to prevent caries and this article provides a summary of the general guidelines and tips on their implementation in relation to caries prevention in children. CPD/Clinical Relevance: This article highlights the importance of caries prevention and the relevant interventions, especially in the context of limited access to health services. These guidelines can be beneficial for all dental health professionals.